IBM z/OS V2R2 JES2, JES3, and SDSF - Winnard, Keith (IBM redbooks, 2015)
This IBM Redbooks publication helps you to become familiar with the technical changes that were introduced into the JES2 JES3, and SDSF areas with IBM z/OS V2R2. Changes include: JES2 updates that are related to z/OS V2R2, JES2 updates that are related to z/OS V2R2, and changes in SDSF in z/OS V2R2. --